PUBLIC PRIVATE PARTNERSHIP DALAM PROGRAM PENGOLAHAN SAMPAH MENJADI ENERGI LISTRIK (PSEL) DI TPA PUTRI CEMPO, KOTA SURAKARTA - Salma Alifia Azzahra, Abrilla; Rina Herawati, Augustin; Purnaweni, Hartuti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Putri Cempo Landfill is the only final waste processing site in Surakarta City. The current open dumping management system will not solve the increasing waste problem. The Public Private Partnership (PPP) can facilitate sustainable waste management by combining the resources and expertise of both the public and private sectors. This study aims to analyze the implementation of the PPP in the Waste-to-Energy (PSEL) Program at the Putri Cempo Landfill, Jebres District, Surakarta City. The PPP process has taken more than 10 years, resulting in repeated delays in the operational target of PSEL Putri Cempo from the original plan. This study uses a descriptive qualitative method, collecting data through interviews, observations, and documentation. The results are analyzed using Matos & Gonçalves' (2020) theory, focusing on contract provisions, regulations and legislative aspects, organizational factors, stakeholder participation, transparency and accountability, budget affordability, and monitoring systems. Supporting factors in this program align with Xiong et al.'s (2019) theory, which emphasizes cooperation, trust, and good communication between the government, private sector, and community. Matos & Gonçalves' (2020) theory was also used to analyze inhibiting factors, such as early project analysis that did not fully align with field conditions. Additionally, an unbalanced risk allocation between the Government and private sector posed a significant challenge, leading to delays in the PSEL's operation. This study recommends that the Surakarta City Government strengthen its understanding of PPP, establish a clear risk management plan with the private sector, and increase public education on waste sorting and the 3R movement (Reduce, Reuse, Recycle). The private sector is also encouraged to engage in Corporate Social Responsibility (CSR) activities by involving the surrounding community in empowerment programs.